Case Report: Rhabdomyolysis following initiation of tirzepatide - Bodanowitz, Jonas Michael; Mattes, Isabell; Loebermann, Micha; Fritzsche, Carlos (Frontiers in Pharmacology, 2025)
We present the case of a 66-year-old woman who developed weakness, nausea, and vomiting accompanied by markedly elevated creatine kinase levels after first treatment with an increased dose of tirzepatide. Laboratory findings were consistent with rhabdomyolysis and normalized within 4 days following discontinuation of tirzepatide and initiation of supportive intravenous fluid therapy. The temporal relationship strongly suggests tirzepatide as a likely trigger. Off-label use, particularly for weight loss, should be avoided and approached with caution. To the best of our knowledge, this is the first reported case of rhabdomyolysis following the initial administration of tirzepatide.